Mechanical properties and impact resistance of hybrid fibre-reinforced high strength concrete / Yew Ming Kun - Yew, Ming Kun (2012)
Concrete is the most widely used construction material since it has the lowest ratio between strength to cost as compared to other available materials. Over the years many researchers have been able to overcome the inherent weaknesses of concrete thereby making it significantly more suitable for a wide variety of applications. The introduction of reinforcement by short discrete fibres (steel, nylon and polypropylene) that are randomly distributed can be practiced among other that remedy weaknesses of concrete such as brittleness, low crack growth resistance, low durability, etc. Fibre-reinforced concrete is a composite obtained by adding a single type or a blend of fibres to the concrete mix. The use of one type of fibre alone helps to eliminate or reduce the effects of only a few specific undesirable properties. Based on previous studies, the addition of two types of fibres in a suitable combination would help to improve more properties of concrete amongst the fibres. This aspect of combining the fibres, i.e. hybridizing the fibres in a rational manner to derive maximum benefits, is investigated in a research on very high strength concrete. High performance fibres- reinforced concrete, with matrix strength of about 100 MPa was used. An attempt was made resulting in a concrete mix suitable for practical use, with the required workability, density, etc. This was achieved by making use of proper admixtures including silica fume and superplasticizers. The amount and type of fibres to be used in the hybrid composites were planned such that the strength properties of the hybrid fibres behaviour could be evaluated. The basic properties of the hybridized material evaluated and analyzed extensively were the mechanical properties of the material. The various fibre types used in diverse combinations included macro and micro fibres of steel, nylon and polypropylene. Control mixes and double fibre hybrids were investigated. Along with basic mechanical properties, modified cube compressive, non-destructive test (ultrasonic pulse velocity,dynamic modulus of elasticity and static modulus of elasticity) and impact resistance tests were also carried out. Results from previous studies indicated that more attractive engineering properties were observed associated with different fibre types when hybridized with macro and micro fibres of steel and nylon demonstrated maximum strength. The volume fraction of macro fibres used for any of the mixes was 0.4% and 0.9% of steel fibres respectively and it appears that this macro fibre volume fraction is high enough to observe maximized strength properties in the hybrids. These amounts of fibres appear to be high enough to make the post peak response of the matrix insensitive to the addition of small dosages (0.1% Vf) of other fibres, such as nylon and polypropylene micro fibres.